PKM Pembuatan Cairan Handsanitizer dalam Peran Serta Penanganan Covid-19 Berdasarkan Instruksi Presiden Nomor 4 Tahun 2020 Bersama PCM Kramat Jati dan Pemuda Muhammadiyah Kramatjati Jakarta Timur, DKI Jakarta - Marjan Miharja; Erwin Syahruddin; Gunawan Gunawan; Meydi Nabillah; Rizal Apriyanto; M. Kholilurrahman; Rusnandi Rusnandi (Jurnal Nasional Pengabdian Masyarakat, 2020)
The spread of Covid 19 has become one of the people's concerns even though at the time of the initial existence of this virus, various efforts in the form of appeals from the government had not really been obeyed by the community. In fact, most people think that the virus will not be as widespread as in the country where it first spread. Various hoaxes regarding weather and climate conditions in Indonesia as conditions that will not cause widespread spread or hoaxes related to ingredients or drugs that are considered to prevent the emergence of Covid 19 have actually been able to influence the public not to fully consider this virus as a threat. However, along with the public's concern about this virus, other impacts have emerged. The implementation of social distancing has had other impacts. In the form of social and economic impacts on society. With the above conditions, we, from STIH IBLAM, conduct a Community Service study program or what is commonly called PKM which with this activity we try to embrace the partnership of the Muhammadiyah Cawang East Jakarta Youth to produce useful products. The product that we will produce is a Hand Sanitizer which can be used to reduce the possibility of transmitting the pandemic outbreak that is currently happening. With our partnership, Pemuda Muhammadiyah making these products with current conditions is indeed not easy, but with the existing obstacles we try to keep making products that we mean with basic ingredients that are safe for our environment. The products we produce will be donated to the surrounding community in connection with the COVID-19 outbreak, maintaining cleanliness and maintaining a healthy environment which is one of the government's programs and recommendations, so that the spread of COVID-19 can be reduced and is also a preventive measure so that the outbreak does not get worse. extends. This PKM activity is carried out by Class 52.S1 of the STIH Iblam Department of Business Law in collaboration with the Cawang Muhammdiyah Youth partnership. The purpose of this activity is to meet the needs of the community for the importance of cleanliness by using safe materials and also to help the community by subsidizing hand sanitizers in the midst of the economic crisis due to the current pandemic. Our target is to assist the government in reducing the spread of the pandemic outbreak, as well as helping the government foster a sense of discipline in personal and environmental hygiene for the community, because personal and environmental hygiene will help us through this pandemic because cleanliness is the key for us to get through the current pandemic.